Perception of Costa Rican market about the use of prefabricated trusses with wood from forest plantations and joined with metal plates - Rivera-Tenorio, Monzerrath (2018)
In housing construction, the most efficient structures to support the loads coming from roofs correspond to the trusses. When it comes to manufacturing them with wood, an important point of these are the joints. Currently the use of metal plates has been introduced for these unions, however, the market still knows little about them and its possibility of use in wooden houses. Therefore, this study reports a first qualitative survey by means of a survey stratified of the use of wooden trusses with metal plates fabricated with plantation wood in Costa Rica. It was found that 100 % of respondents consider wood as a viable material for construction, for storing carbon dioxide and for being a renewable resource. In addition, most consider that the wood from trees growing in plantations in Costa Rica is of good quality. However, only 28 % prefer the use of trusses as a structural element in roofs and 40 % agree that the use of the metal plate is a good technological option. According to this first market survey of the wooden truss with metal plate, 80 % of respondents would be willing to acquire it; giving it a price range between ¢ 45 000 to ¢ 50 000 per truss.